Chalinochromis cyanophleps, a new species of cichlid fish (Teleostei: Cichlidae) from Lake Tanganyika - Kullander, Sven O.; Karlsson, Mikael; Karlsson, Magnus; Norén, Michael (Zootaxa, 2014)
Chalinochromis cyanophleps is described from nine specimens, the largest 129 mm SL, from Namansi. It differs from other species of Chalinochromis in plain trunk colouration, absence of black stripes on the head, relatively narrow lips, presence of tricuspid jaw teeth, and presence of five rather than four dentary lateralis foramina. The blue iridescent stripe below the eye is shared with other lamprologin cichlids, but is broader and more conspicuous in C. cyanophleps. Chalinochromis cyanophleps occurs at depths between 6 and 45 m in rocky habitats along the Tanzanian coast of Lake Tanganyika, from Mvuna Island south to Kalala Island, a stretch of about 90 km. Field observations were made of specimens up to 18 cm total length. The COI DNA barcode sequence differs by 1.8% from that of C. popelini.